2011
DOI: 10.1177/1947601911423940
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Stromal Myofibroblast and Extracellular Matrix in Tumor Angiogenesis

Abstract: Tumor angiogenesis, the building of blood vessels in an expanding tumor mass, is an elegantly coordinated process that dictates tumor growth and progression. Stromal components of the tumor microenvironment, such as myofibroblasts and the extracellular matrix, collaborate with tumor cells in regulating development. Such myofibroblasts and the extracellular matrix have ever-expanding roles in the angiogenic process as well. This review summarizes how stromal myofibroblasts and the extracellular matrix can modul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(90 citation statements)
references
References 92 publications
3
83
0
4
Order By: Relevance
“…The stroma includes cancer-associated fibroblasts (CAFs), inflammatory cells and endothelial cells, which facilitate EMT induction and drive metastatic progression through interaction with cancer cells (Vong & Kalluri 2012). Arnold et al (2002) observed that secretions from normal endometrial fibroblast cells can inhibit proliferation of Ishikawa cells.…”
Section: Role Of Tumor Microenvironmentmentioning
confidence: 99%
“…The stroma includes cancer-associated fibroblasts (CAFs), inflammatory cells and endothelial cells, which facilitate EMT induction and drive metastatic progression through interaction with cancer cells (Vong & Kalluri 2012). Arnold et al (2002) observed that secretions from normal endometrial fibroblast cells can inhibit proliferation of Ishikawa cells.…”
Section: Role Of Tumor Microenvironmentmentioning
confidence: 99%
“…58,111,112 It has been estimated that a tumour cannot grow beyond a volume of 2 mm 3 without the development of new vessels to provide the proliferating cells with oxygen and nutrients. 58 Angiogenesis is thus a pivotal step in tumour development, and is one of the so-called 'hallmarks of cancer'.…”
Section: Vasculature/endotheliummentioning
confidence: 99%
“…For more detail the reader is referred to the review by Vong and Kalluri. 58 During tumour progression, matrix remodelling leads to the release of matrixassociated growth factors which may function to suppress or induce tumour growth.…”
Section: Extracellular Matrixmentioning
confidence: 99%
“…A Study have showed that TGF-β1 expressing exosomes can initiate the development of fibroblasts to myofibroblasts [56]. Myofibroblasts release considerable matrix remodeling proteins within the tumor microenvironment and contribute to tumor angiogenesis [57]. Cancer exosome-induced stimulation of fibroblasts could favor tumor angiogenesis.…”
Section: Mini Reviewmentioning
confidence: 99%